1999
DOI: 10.1002/(sici)1097-4628(19990929)73:14<2887::aid-app12>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Structural and conformational changes of regeneratedAntheraea pernyi silk fibroin films treated with methanol solution

Abstract: ABSTRACT:The regenerated Antheraea pernyi silk fibroin films were prepared from calcium nitrate solution and crystallized with aqueous methanol solution. The structural and conformational changes were investigated by the X-ray diffraction method and infrared spectroscopy upon methanol treatment. The concentration and treatment time of aqueous methanol solution have a great influence on the conformation of regenerated films. The conformational change from a random coil to ␤-sheet structure was occurred within 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 15 publications
3
33
0
2
Order By: Relevance
“…In contrast, the natural Ap-SF fiber containing moreˇ-sheet structures has long-term degradation characteristics. It has been reported that the molecular conformation of the Ap-SF materials changes after treatment with methanol solution, ethanol and other organic solvents and changes with temperature [6][7][8][9]. These observations will allow us to adjust the molecular conformation of Ap-SF based biomaterials which would be applied in tissue engineering or tissue inducing, and to control the biodegradation rates, so as to satisfy numerous tissue regeneration requirements.…”
Section: Free Amino Acid Analysis Of Ap-sf Degradation Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the natural Ap-SF fiber containing moreˇ-sheet structures has long-term degradation characteristics. It has been reported that the molecular conformation of the Ap-SF materials changes after treatment with methanol solution, ethanol and other organic solvents and changes with temperature [6][7][8][9]. These observations will allow us to adjust the molecular conformation of Ap-SF based biomaterials which would be applied in tissue engineering or tissue inducing, and to control the biodegradation rates, so as to satisfy numerous tissue regeneration requirements.…”
Section: Free Amino Acid Analysis Of Ap-sf Degradation Productsmentioning
confidence: 99%
“…The results indicated that the regenerated Ap-SF, like B. mori silk fibroin and collagen, can support hBMSCs attachment, growth and phenotypic maintenance, and has better biocompatibilities for hBMSCs in vitro culture. Based on these features, interest has arisen into the use of Ap-SF as a starting material for advanced biomedical applications such as cell culture substrates, surgical mending materials and tissue engineering scaffolds [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…By studying the attachment, morphology, growth and phenotype of human bone marrow derived mesenchymal stem cells (hBMSCs) cultured on Ap-SF films, it was found that Ap-SF, such as B. mori silk fibroin and collagen, could support hBMSC attachment, growth and phenotypic maintenance, and has better biocompatibilities for in vitro culture of hBMSCs [12]. Based on these features, interest has risen in the use of Ap-SF as a starting material for advanced biomedical applications such as cell culture substrates, surgical mending materials and tissue engineering scaffolds [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…최근에 들어 세포 및 조직에 대한 실크단백질의 생체 적합성이 검증되고 있어 이를 활용한 실크단백질을 이용 한 의료용 소재 개발 연구에 관한 관심이 증가하고 있다 (Vepari and Kaplan 2007, Meinel et al 2005, Minoura et al 1995. 고막재생용 실크 패치 (Kim et al 2010), 치과용 실크 차폐막 (Seok et al 2013, Kweon et al 2010a, 조직 공학용 실크 지지체 (Cho et al 2013, Zhao et al 2011, 약물전달용 매트릭스 ) 등 다양한 생체재 료로서 실크 단백질을 활용하기 위한 연구 개발이 추진 되고 있다 (Silva et al 2008, Hu et al 2006, Kweon and Park 1999, Tsukada 1986 …”
Section: 서 론unclassified